THE NATURE OF THE FINANCIAL ACCOUNTING PROCESS. - May, George O. (The Accounting Review, 1943)
Abstract This article focuses on the nature of financial accounting process. Accounting has been defined by a committee of the American Institute of Accountants as "the art of recording, classifying and summarizing, in a significant manner and in terms of money, transactions and events which are, in part at least, of a financial character, and interpreting the results thereof." It is an art, not a science, but an art of wide and varied usefulness. The purely recording function of accounting, though indispensable, concerns only technicians. Its analytical and interpretive functions are of two kinds. One type of analysis is intended to afford aid to management in the conduct of business and is of interest mainly to executives. The other type leads to the presentation of statements relating to the financial position and results of operations of a business for the guidance of directors, stockholders, credit grantors, and others. This process of financial accounting, therefore, possesses a wide importance for persons who are neither accountants nor executives.